Direct data-driven control approach of reference shaping for two degree of freedom control. Issue 1 (31st December 2022) - Suzuki, Motoya; Kaneko, Osamu
Abstract : In this study, we propose a novel data-driven approach for control of two degrees of freedom systems. The proposed method uses one-shot experimental data to derive the reference governor for improving control performance. The reference governor consists of feedback-feedforward controller, desired transfer function, and virtual feedforward controller. Virtual feedforward controller can be obtained using data-driven control approach such as ERIT, FRIT, and VRFT. Since a model is not required in our method, the cost related to modelling can be reduced. Numerical simulations were used to validate the proposed method. Verification results demonstrate that the desired control response was achieved by reference shaping alone, with the feedback and feedforward controllers not requiring any updates. The proposed method can realize the desired control performance in cases where the plant is non-minimum-phase system.